PERBEDAAN PENJUALAN SEBELUM DAN MASA PANDEMI COVID-19 PADA PT. PINUS MERAH ABADI - Toni, Angga Aprian (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
The Covid-19 case first appeared in Wuhan, China, at the end of 2019 the spread of this virus pandemic was so fast from human to human, from one country to another, that it spread throughout the world, including Indonesia. This study aims to find out how the company's sales were before and during the Covid-19 pandemic. Is there a significant difference from the company's operations?. Can good and efficient or effective company sales contribute positively to the company? Based on the results of research that has been done about Analysis of Differences in Company Sales PT. Pinus Merah Abadi Before and During the Covid-19 Pandemic can be summarized as follows: 1. In 2019 before the covid-19 pandemic the total sales of PT Pinus Merah Abadi's wafers amounted to 3,929 (million rupiah) with an average annual sales of 327.41 (million rupiah). 2. Whereas in 2020, after the Covid-19 pandemic, PT Pinus Merah Abadi's total sales amounted to 3,554 with an average annual sales of 296.16 (million rupiah). There is a significant difference between the sales of the company PT Pinus Merah Abadi, both before the Covid-19 pandemic and during the Covid-19 pandemic. From the results of the research using the different t test above, it is proven that there is a significant difference between sales results in 2019 and 2020. This based on the test results, namely t count = 3.31 > t table 1.782 at a significance level of 5%. Keywords: Company Sales, Before and During the Covid-19 Pandemic.